1997
DOI: 10.1038/sj.bjp.0701370
|View full text |Cite
|
Sign up to set email alerts
|

Negative chronotropic actions of endothelin‐1 on rabbit sinoatrial node pacemaker cells

Abstract: 1 The eects of endothelin-1 (ET-1) on sinoatrial (SA) node preparations of the rabbit heart were studied by means of whole-cell clamp techniques. 2 ET-1 at 1 nM slowed the spontaneous beating activity and rendered half of the cells quiescent. At a higher concentration of 10 nM, the slowing and cessation of spontaneous activity were accompanied by hyperpolarization. 3 In voltage-clamp experiments, ET-1 decreased the basal L-type Ca 2+ current (I Ca(L) ) dose-dependently with a half-maximal inhibitory concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
16
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 45 publications
10
16
1
Order By: Relevance
“…[56][58]). Tanaka and colleagues demonstrated activation by ET-1 in rabbit SAN cells of an inwardly rectifying K + current similar to that seen here, also showing this to be Ba 2+ -sensitive and to carry outward current over potentials relevant to the diastolic potential range [21]. Drici and colleagues have demonstrated that ACh-induced AV block in guinea-pig hearts is prevented by tertiapin at concentrations including that used here, without non-selective effects of tertiapin on other important cardiac ionic currents [47].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…[56][58]). Tanaka and colleagues demonstrated activation by ET-1 in rabbit SAN cells of an inwardly rectifying K + current similar to that seen here, also showing this to be Ba 2+ -sensitive and to carry outward current over potentials relevant to the diastolic potential range [21]. Drici and colleagues have demonstrated that ACh-induced AV block in guinea-pig hearts is prevented by tertiapin at concentrations including that used here, without non-selective effects of tertiapin on other important cardiac ionic currents [47].…”
Section: Discussionsupporting
confidence: 83%
“…Ono and colleagues also reported a modest reduction in delayed rectifier (I K ) tails across a wide range of voltages for spindle-shaped cells and up for voltages up to ∼0 mV for rod-shaped cells, accompanied in both SAN types by positively shifted (∼+5–+14 mV) I K activation [23]. Tanaka and colleagues also showed suppression of SAN I K by ET-1, though they did not study the voltage-dependence of the effect [21]. The activation V 0.5 values under control conditions for the tail currents investigated in this study are within the range reported previously for AVN I Kr [33], [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the PV cardiomyocytes with pacemaker activity, endothelin‐1 was demonstrated to have an antiarrhythmic potential due to decreasing the PV beating rates and triggered activity. Similar to that in this study, endothelin‐1 also has been shown to decrease the beating rates in rabbit sinoatrial pacemaker cells with the inhibition of the I Ca‐L 25 . These results suggest the complex effects of endothelin‐1 on PV cardiomyocytes with and without pacemaker activity.…”
Section: Discussionsupporting
confidence: 89%
“…Endothelin‐1 has negative chronotropic effects on guinea pig atria 24 and also on rabbit sinoatrial nodal cells 25 . In tissue experiments, we found a negative chronotropic effect in the PVs.…”
Section: Discussionmentioning
confidence: 58%